2018
DOI: 10.1007/s00253-018-8837-4
|View full text |Cite
|
Sign up to set email alerts
|

Integrated network analysis reveals the importance of microbial interactions for maize growth

Abstract: Microbes play a critical role in soil global biogeochemical circulation and microbe-microbe interactions have also evoked enormous interests in recent years. Utilization of green manures can stimulate microbial activity and affect microbial composition and diversity. However, few studies focus on the microbial interactions or detect the key functional members in communities. With the advances of metagenomic technologies, network analysis has been used as a powerful tool to detect robust interactions between mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(51 citation statements)
references
References 64 publications
3
46
0
Order By: Relevance
“…The functional stability of microbial communities depends on the complicated microbe-microbe interactions [41]. Studies about soil microbiota con rm that the network complexity is consistent with the ability to cope with the diverse environmental changes [42]. After exposure to azithromycin, the airway microbiota networks in our study become simple, indicating the attenuated resilience.…”
Section: The Effects Of Azithromycin On Airway Microbial Interactionssupporting
confidence: 63%
“…The functional stability of microbial communities depends on the complicated microbe-microbe interactions [41]. Studies about soil microbiota con rm that the network complexity is consistent with the ability to cope with the diverse environmental changes [42]. After exposure to azithromycin, the airway microbiota networks in our study become simple, indicating the attenuated resilience.…”
Section: The Effects Of Azithromycin On Airway Microbial Interactionssupporting
confidence: 63%
“…The functional stability of microbial communities depends on the complicated microbe-microbe interactions [40]. Studies about soil microbiota confirm that the network complexity is consistent with the ability to cope with the diverse environmental changes [41]. After exposure to azithromycin, the airway microbiota networks in our study become simple, indicating the attenuated resilience.…”
Section: The Effects Of Azithromycin On Airway Microbial Interactionssupporting
confidence: 60%
“…On the other hand, members of Bacteroidetes accounted for less than 7% of module hubs and connectors and Verrucomicrobia members accounted for 16.67% in tall cultivars. Module hub and connector OTUs have been proposed as putative keystone taxa and ecological generalists, critical for maintaining community structure and function; peripherals on the other hand being considered isolated specialists 41,[69][70][71][72][73][74] . As such, Proteobacteria seem to be critical in maintaining the structure and functionality of bacterial communities in wheat rhizosphere for both tall and semi dwarf cultivars and these results are in accordance with data provided by Oberholster et al 71 , who also found Proteobacteria to be important keystone taxa for sorghum and sunflower rhizospheres.…”
Section: Resultsmentioning
confidence: 99%